PENGARUH HARGA DAN PROMOSI MELALUI SOSIAL MEDIA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN KOPI LAIN HATI BANDA ACEH - Maulida, Zenitha; Nurbismi, Nurbismi; Roza, T Andi; Nurhafiah, Nurhafiah (SI-MEN, 2024)
Abstract ​The aim of this research is to determine the influence of prices and promotions through social media on consumer purchasing decisions for coffee Lain Hati Banda Aceh, both partially and simultaneously. The total sample for this research was 99 respondents. Research data was collected through questionnaires distributed to respondents. Research data was analyzed using a multiple linear regression model. Hypothesis testing uses F test analysis and t test to determine the influence of the independent variable on the dependent variable simultaneously and partially at a confidence level of 95% (α = 0.05). The results of research based on simultaneous tests show that the variables Price and Promotion via Social media have a significant effect on Consumer Purchase Decisions of Banda Aceh's Lain Hati Coffee. The partial test also shows that the Price variable has a significant effect on the Purchase Decision of the Banda Aceh Other Hati Coffee Consumers and the Promotion variable through Social Media has a significant effect on the Purchase Decision of the Banda Aceh Other Hati Coffee Consumers. Keywords: Price, Promotion via Social Media and Purchasing Decisions.